Feature Articles on Nutrition and Obesity Management (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Obesity represents the most prevalent metabolic disease in the world, posing a significant public health threat. Obesity shortens life expectancy by increasing the risk of developing comorbidities such as type 2 diabetes or cardiovascular disease. A better understanding of the ethiopathology of excess adiposity represents the pillar on which to base the effective management of obesity. In this sense, this reprint expands our knowledge about the wide array of drivers that can facilitate or contribute to the development of obesity. Moreover, some of the latest progress made in lifestyle, pharmacological and surgical approaches in the treatment of obesity are summarised. Novel concepts regarding the different obesity phenotypes, the use of telemedicine for the treatment of overweight and obesity, or the use of personalised avatars in the management of obesity are also reviewed. This reprint will be of interest for specialists in Endocrinology and Nutrition, but also for any individual interested in health issues related to nutrition.